2017
DOI: 10.1111/sltb.12338
|View full text |Cite|
|
Sign up to set email alerts
|

The Association Between Political Violence and the Connection Between Bullying and Suicidality Among Palestinian Youth

Abstract: We examined the association between protracted political violence and the connection between bullying and suicidality among Palestinian adolescents. Data were collected from a representative sample of Palestinian students (N = 5,713) from 100 schools in the West Bank and East Jerusalem who completed an in-class survey. Students who were victims of bullying or bully victims who were exposed to political violence were at higher risk for suicide attempts compared to students who were victims of bullying or bully … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…In the present study with college students, the prevalence of suicide ideation was three times higher and the prevalence of suicide attempts was two times higher than in the 2002 Ukrainian national sample from Bromet et al (2007) study. Traumatic events have been linked with increased suicidality in previous research (e.g., Abdeen et al 2018). Several political crises have taken place in Ukraine since 2002, including the Orange Revolution of 2004, the Revolution of Dignity of 2014, and ongoing military conflict in Eastern Ukraine (Burlaka et al 2018).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In the present study with college students, the prevalence of suicide ideation was three times higher and the prevalence of suicide attempts was two times higher than in the 2002 Ukrainian national sample from Bromet et al (2007) study. Traumatic events have been linked with increased suicidality in previous research (e.g., Abdeen et al 2018). Several political crises have taken place in Ukraine since 2002, including the Orange Revolution of 2004, the Revolution of Dignity of 2014, and ongoing military conflict in Eastern Ukraine (Burlaka et al 2018).…”
Section: Discussionmentioning
confidence: 87%
“…Among females, the rate increased from 4.0 per 100,000 in 1999 to 5.8 per 100,000 in 2014 (Curtin et al 2016). Similarly, another study, which included data from 14,738 suicide cases (age group 15-24) in 15 European countries, documented that suicide rates were significantly higher for males (5.5-35.1) than for females (1.3-8.5) (Värnik et al 2009). Moreover, a study in South Korea, which included suicide rates from 2006 to 2008, also revealed that suicide rate was higher in males than in females; however, the rate was also found to be higher among older people than among younger people (Cheong et al 2012).…”
Section: Age and Sex Differences In Suicidalitymentioning
confidence: 96%
“…Figure 1 shows the suicide rates (smoothed and age-adjusted) in the contiguous U.S. counties from 2008 to 2014 using natural break classification [ 20 ]. Overall, suicide rates were much higher in the western counties compared to those in the other regions.…”
Section: Resultsmentioning
confidence: 99%
“…However, risk factors may be different across geographic regions, and risk factors may also change over time. For instance, political violence, an uncommon risk factor for suicide in adolescents, is reportedly associated with suicide among Palestinian youths [ 20 ] and periodical economic recession was also found to be associated with elevated suicide rates [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Reports from Israel, Lithuania, Luxembourg, Latin-America [6], and across the continents consistently show how disastrous bullying involvement can be [31]. Exposure to the country's political violence intensifies the primary problem [32]. These youth groups, living in a geographical location who always experience war, should be protected, and strategies must be developed to help them.…”
Section: Mediators Of Bullyingmentioning
confidence: 99%